2021
DOI: 10.1088/1748-9326/ac22c1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing risks of crop failure and water scarcity in global breadbaskets by 2030

Abstract: As the greatest water user in the world, the agricultural sector is vulnerable to changes in climate and water resource availability. Understanding the impact of these changes on crop yield is critical in order to achieve and maintain global food security. We analyze output from an ensemble of Agricultural Model Intercomparison and Improvement Project models to project the probability of rice, soybean, maize, and wheat yield failures across global and national breadbaskets through mid-century. The probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Other studies across the US have also shown that combined effects of heat and drought can further intensify water scarcity, with impacts on crop production in irrigated agriculture (Luan et al 2021). All these changes increase the risks of water scarcity and yield reductions in global irrigated areas (Caparas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies across the US have also shown that combined effects of heat and drought can further intensify water scarcity, with impacts on crop production in irrigated agriculture (Luan et al 2021). All these changes increase the risks of water scarcity and yield reductions in global irrigated areas (Caparas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To sustain irrigated agriculture and to buffer when water demands temporally exceeds supply, for example during droughts, proper management of agricultural water is central (Singh 2014, Caparas et al 2021. We evaluate the impacts of conjunctive groundwater use as a management strategy for water scarcity alleviation, by diluting surface water at instances where salinity levels exceed crop specific tolerance levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final step of this process, the ranked criteria are combined to provide spatial indications on where biochar should be prioritized. (Caparas et al, 2021) or excessive fertilizer use (West et al, 2014). Biochar, with its diverse positive effects, can support agronomy by countering many such challenges (Lehmann et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Global warming results in food insecurity (due to foundering agriculture and infrastructure) that contributes appreciably to the development of obesity 13 ; in this context, crop yield failure across global food providers is projected to rise up to 25 times by 2050. 14 Even now, food insecurity is a contributor to the development of obesity by virtue of reliance on unhealthy energy intake, including refined (ie, highly processed) foodstuffs. 15 Whereas obesity and its metabolic consequences due to unhealthy diets can lead to NAFLD, poverty and food insecurity may also lead to malnutrition.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%